P812 Natural disease course of inflammatory bowel disease unclassified in a prospective European population-based inception cohort—the Epi-IBD cohort. (16th January 2018) - Burisch, J; Ellul, P; Arebi, N; Kaimakliotis, I; D'Inca, R; Andersen, V; Belousova, E; Hernandez, V; Vegh, Z; Turcan, S; Magro, F; Kupcinskas, L; et al.
Abstract: Background: The precise diagnosis of inflammatory bowel disease (IBD) cannot always be established. Thus, a proportion of patients will be diagnosed as IBD Unclassified (IBDU). A significant proportion of these patients will remain unclassified throughout their disease course. Only very few population-based cohorts have investigated the disease course of IBDU. Methods: The Epi-IBD cohort is a prospective population-based cohort of 1289 unselected, uniformly diagnosed patients with IBD diagnosed in 2010 in centres from Western and Eastern European countries. Clinical data were captured prospectively throughout the follow-up period. The aim of the study was to investigate the disease course and prognosis of patients diagnosed with IBDU from diagnosis and during the first 5 years of follow-up. Results: A total of 112 (9%) patients were initially diagnosed with IBD). Patient characteristics are shown in Table 1. After 5 years of follow-up, 28 (25%) patients changed diagnosis to either ulcerative colitis (UC) ( n = 20, 71%) or Crohn's disease (CD) ( n = 8, 29%) while 84 (7% of the total cohort) remained as IBDU. The median time to a definite IBD diagnosis was 7 months (range: 1–63) with no difference between those changing to UC or CD. A total of 17 (15%) patients were hospitalised for their IBD during follow-up after a median of 10 months (range: 0–63). Of those, 9 (45%) patients changed diagnosis to UC during follow-up, while no patient changing diagnosis to CD was hospitalised. 8 (7%) patients had surgery (7 colectomies, 1 resection) after a median of 19 months (range: 3–63). Most surgeries ( n = 6, 75%) were performed in patients who changed diagnosis to UC, and 3 of those led to a definite diagnosis of UC where the other 3 were performed after the change of diagnosis. No patient changing diagnosis to CD had surgery. The cumulative exposure to medical treatments in IBDU patients including those who later changed to a definite is shown in Figure 1. Almost all patients ( n = 107, 96%) received 5-ASA, while 11 (10%) patients received biologicals of which 5 remained as IBDU. Conclusions: In this population-based inception cohort, after 5-years 7% of patients remain without a definite diagnosis of IBD. The rate of surgery and the use of biological therapy in patients changing diagnosis to UC were higher than what is observed in patients diagnosed initially with UC.